Impacts of Wild Pigs on Space Use and Movements of Wild Turkeys During Autumn and Winter - Travis E. Stoakley; Stephen J. Zenas; Vienna R. Brown; Mark D. Smith; William D. Gulsby; Bret A. Collier; Stephen S. Ditchkoff (Ecology and Evolution)
ABSTRACT Wild pigs (Sus scrofa) affect native flora and fauna in the areas they invade, including ground‐nesting birds. While results from camera‐based studies have suggested that wild pigs could spatiotemporally impact resource selection of wild turkeys (Meleagris gallopavo), there has yet to be published a foundational mechanism proposed to support such impact. Additionally, while the autumn and winter seasons serve as an important period for improving body condition for spring breeders like wild turkeys, there exists a knowledge gap in the literature with respect to potential impacts of wild pigs on wild turkeys during this non‐breeding period. We proposed a novel methodology for exploring the spatiotemporal relationship between wild pigs and wild turkeys through the co‐employment of a camera survey to estimate wild pig activity and GPS units to monitor wild turkey space use. Our study monitored 12 wild turkeys across a 9000‐ha study area in east‐central Alabama during the autumn and winter seasons. We hypothesized that wild turkeys would exhibit reduced use and altered movement rates in areas with greater wild pig activity. Our results suggested that wild turkeys displayed slower rates of movement and had lower predicted probabilities of daytime use and roost site selection in areas of greater wild pig activity. Our study was limited to one season, but paired with previous camera‐based studies, we propose that wild pigs could serve as a perceived disturbance risk to wild turkeys, leading to avoidance of areas with greater wild pig activity. We also believe wild pigs could compete with wild turkeys for hard mast, which could explain the negative relationship between wild pig activity and predicted probabilities of daytime use among female wild turkeys in hardwood and riparian areas. Our study showcases the potential value in pairing multiple spatiotemporal data types (e.g., GPS‐data and camera‐based estimates) in future interspecific wildlife research.